Neuroeducation in the classroom: using multimodal neuroimaging to predict mathematical learning - Gil Lorenzo Valentín., Noelia Ventura-Campos, Mercedes Ventura, (Opción, 2019)
Mathematical learning difficulties are frequent in the classroom. The lack of early intervention can have serious educational consequences, and these math difficulties can even continue into adulthood. This article briefly reviews BEHAVIORAL and neuroimaging research on both dyscalculia and the mathematical learning process. It concludes that longitudinal studies using multimodal neuroimaging techniques are the key to studying individual variability in children with a low level of mathematical performance and the brain areas that predict improved learning. The results of these studies will make it possible to implement suitable evidence-based interventions in educational settings. Thus, neuroeducation will help to achieve better teaching and learning in the classroom.